Economic benefits and returns to rural feeder roads - Stifel, David; Minten, Bart; Koru, Bethlehem (International Food Policy Research Institute, 2012)
We estimate households’ willingness-to-pay for rural feeder roads in Ethiopia. Using a quasi-experimental setting, we find that the benefits of reducing transportation costs by 50 US dollars per metric ton of goods (agricultural surplus, purchased consumption goods, purchased agricultural inputs) would result in benefits worth roughly 35 percent of household consumption. A hypothetical gravel road of 21 km (a road built halfway through the survey site) that lasts 10 years will have an internal rate of return (a measure for the profitability of an investment) that ranges from 12 to 34 percent, using conservative assumptions. These results suggest that investments in rural feeder roads are cost-effective ways to help reduce widespread poverty even in unfavorable settings where small-scale farmers have low levels of marketed agricultural surplus, nonfarm earnings opportunities are negligible, and the provision of motorized transport services is not guaranteed.